Outcomes of an Early Protocol for Dependent Conditioning in Lower Extremity Microsurgical Free Flaps - Seth, Akhil K.; Diamond, Shawn; Iorio, Matthew L. (Journal of Reconstructive Microsurgery, 2017)
Background Free tissue transfer is integral to traumatic, oncologic, and diabetic lower limb reconstruction. However, limited data exist on postoperative dependent conditioning or “dangling.” We report our experience utilizing an early pathway for fasciocutaneous flap dangles.Methods Lower extremity microsurgical reconstructions from December 2014 to December 2016 were reviewed. Postoperative pathway included tissue oximetry and Doppler monitoring. On postoperative day 2, dangling started at 5 minutes three times daily with monitoring for flap congestion, signal loss, or persistent oximetry drop. Dangles were increased daily by 5 minutes per dangle to 20 minutes three times daily.Results Twenty-six patients underwent lower extremity reconstruction and completed an early dangling protocol with anterolateral thigh (n = 23, 88.5%) or medial sural artery perforator (MSAP, n = 3, 11.5%) flaps. Average age and body mass index (BMI) were 53.6 years and 28.6, respectively. Infection (n = 16), trauma (n = 13), exposed hardware (n = 12), and malignancy (n = 3) were common etiologies with most wounds below the knee (n = 23). Flaps were primarily taken on one perforator (n = 17) with an end-to-end arterial (n = 18) and two venous (n = 16) anastomoses. With an 8.7-month follow-up, partial and complete flap loss rates were each 3.8% (n = 1). Mean hospital stay was 7.9 days (range: 6–12 days) with 84.6% (n = 22) of patients on ambulatory care with assistance on discharge.Conclusion Lower extremity microsurgical reconstruction can be performed safely and effectively utilizing a standardized postoperative care and dangling pathway. An early, cautious dangle protocol does not increase complications but affords decreased hospital stays and early flap conditioning. In the absence of complicating factors, such as vascular insufficiency, utilizing a defined protocol in these complex patients allows for enhanced, consistent care.
Keywords: lower extremity flap; microsurgical; free flap; dangle; dependent conditioning